Pathways of migration from gaming to gambling - John, Nisha (Ind Psychiatry J, 2020)
Gaming and gambling have been studied in terms of similarity of its manifestations. There is a dearth of empirical-based evidence for the exploration of pathways to understand the shift from gaming to gambling. A 23-year-old male from a nuclear family was assessed using clinical interview for the pathways for shifting from gaming to gambling. The pathways were personality predispositions, maladaptive coping, interpersonal distress, peer pressure, variable reward anticipation, addiction characteristics in the form of craving, loss of control and use despite having consequences. These findings suggest that there is a need to create awareness among young adults about these potential causes related to transition from gaming to gambling.